Migration of Birds of Prey Through The Western Caucasus in Autumn - Alexander G. Perevozov (Пернатые хищники и их охрана)
Research took place in the Caucasian Nature Reserve and its environs in 2006–2022 in periods from August to November during expeditions and at stations. Raptor migration in the study area occurs across a wide area, with greater intensity in the Malaya Laba River valley. Agricultural fields are located in foothill locations, where birds rest and feed in case of bad weather at higher elevations, and when conditions improve continuing over the Main Caucasian Range.